AN EXPRESSION OF SPIRITUAL DEGRADATION AND SOCIAL CRISIS IN THE WORK OF NAVOI (Scientific journal of the Fergana State University, 2023)
The article analyzes the interconnected and harmonious image of family life and crises of social and spiritual life in the work of Navoi.